The mediating role of self-control on the relations between adverse childhood experiences and substance use among adolescents in Uganda - Namusoke, Jane; Amone-P’Olak, Kennedy; Nakanwagi, Carol Chosen; Kibedi, Henry; Mayengo, Nathaniel; Ssenyonga, Joseph; Omech, Bernard (Frontiers in Psychology, 2024)
Objectives: Adverse childhood experiences (ACEs) are established risk factors for undesirable consequences in adolescence and early adulthood, including substance use and a lack of self-control. Based on the Social Bonds Theory (SBT), this study aims to expand our knowledge of the pathways from ACEs and self-control to substance use in adolescence and early adulthood.The extent to which self-control mediates the association between ACEs and substance use was examined in a cross-sectional survey of 358 adolescents and young adults (N = 234, 65.5% girls, mean age 17.7, SD 0.58, range 15-18). Data were gathered using the Adverse Childhood Experiences (ACE-10) questionnaire, the Drug Abuse Screening Test (DAST-10), and the 10-item self-control scale to assess childhood adversity, substance use, and self-control, respectively.Results: ACEs were widely reported and significantly associated with substance use and a lack of selfcontrol. Self-control strongly predicted substance use, independent of ACEs. Among those reporting no ACEs, one to two, three to four, and five or more, there were significant variations in the respondents' substance use (F (3, 400) = 12.69, p =.001). Self-control explained 51.2% (95% confidence interval [CI]: 41%, 61%) of the associations between ACEs and substance use as assessed by linear regression.Self-control is key to understanding why adolescents and young adults with a history of childhood adversity indulge in substance use. Therefore, there is a need to advocate for psychological interventions such as cognitive and behavioural therapy that have demonstrated efficacy in promoting selfcontrol in adolescents and young adults.